2018
DOI: 10.3390/sinusitis3010002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Sinus Problems in Farm and Non-Farm Populations of Rural Saskatchewan, Canada

Abstract: Although sinus problems have long been recognized as the most common respiratory symptoms associated with agricultural work, there is a scarcity of recent studies and/or reliable estimates as to the true prevalence or risk factors of sinus problems related to farming. The aim of this study was to determine the prevalence of sinus problems in farming and non-farming rural populations and further investigate the association of individual (for example life-style, occupational), contextual (e.g., environmental), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(101 reference statements)
1
1
0
Order By: Relevance
“…Based on the results, among various types of land cover, the urban setting was the most important factor directly affecting CRS occurrence. Our results are consistent with some studies showing a higher prevalence of allergic rhinitis and nasal symptoms among people born and raised in urban areas than among those in rural areas [ 22 25 ]. The microbial load and diversity accompanied by farm living in rural areas have been suggested as a reason for the beneficial effects on respiratory diseases [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results, among various types of land cover, the urban setting was the most important factor directly affecting CRS occurrence. Our results are consistent with some studies showing a higher prevalence of allergic rhinitis and nasal symptoms among people born and raised in urban areas than among those in rural areas [ 22 25 ]. The microbial load and diversity accompanied by farm living in rural areas have been suggested as a reason for the beneficial effects on respiratory diseases [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is supported by the heavy use of fungicide, pesticides, and insecticide (n=4248, 4%) in their residential areas. 18 Similarly, Yu et al 28 found that Asian sand dust (ASD), carried through wind from the Mongolian deserts, is associated with the development of CRS and other respiratory diseases. Yeo et al 29 described the mechanism by which ASD leads to CRS as ASD increases the replication of rhinovirus leading to disturbance in the local immunological environment, rendering the nasal mucosa more susceptible to dust and microbes.…”
Section: Discussionmentioning
confidence: 99%